Experimental investigation and finite element analysis of reinforced concrete beams strengthened by fibre reinforced polymer composite materials : A review - Solahuddin, Azuwa; Fadzil, Mat Yahaya (Elsevier B.V., 2024)
As a composite material, fibre reinforced polymer (FRP) has many uses. Incorporating FRP composite material enhances the reinforced concrete beams’ (RCB) performance, properties and behaviour as external reinforcement. A summary of how different FRP influences the RCB properties should be studied. This review paper discusses the use of FRP to reinforce RCB and briefly describes the topic. Previous experimental studies and finite element analysis (FEA) results showed that RCB constructed with FRP significantly improved the axial load, load-deflection, ultimate load, crack propagation, stress-strain distribution, and failure mode of RCB. Since this FRP composite material has superior strength, force, mounting and anchoring properties, it can be used as an alternate exterior reinforcement in RCB. The structural behaviour and performance of RCB can be enhanced by utilising FRP composite material in civil and structural engineering, especially in building construction projects.